Analisis Pengembangan Karier Karyawan di Masa Pandemi Covid-19 - Andini Syafitri; Muhammad Putra Dinata Saragi (Reslaj : Religion Education Social Laa Roiba Journal, 2023)
Basically, in order to get employees who have good performance, a company must make efforts to meet the needs of employees. An agency or company needs to properly control the career development of its employees and avoid work frustration which can lead to decreased employee performance in the company. This study aims to look at efforts to develop employee careers, and the method used in this research is descriptive qualitative research. Data collection techniques using observation, interviews, and documentation. The subjects of this study were several employees who worked at an automotive company in the city of Medan, taken using a purposive sampling technique. The results of this study indicate that employee career development is very promising and so far the employee career development has been quite good in the company. The process of career development in this company is from promotions, job transfers and promotions to the employees concerned. Following up on the findings in this study, the career development of employees of one of the automotive companies in the city of Medan is measured by supporting factors, namely skills, educational background, training, opportunities for development and employee work experience. Keyword : Career Development, Employee, Pandemic, Covid-19.